The Imposition of Sanctions for Children - Rafika Nur; Handar Subhandi Bakhtiar (Faculty of Law, Hasanuddin University, 2020)
In the children criminal justice system in Indonesia, there are two systems of sanctions namely criminal sanctions and sanctions actions. A child who commits a criminal offense may be subject to criminal sanctions or sanctions. Imposing sanctions for children becomes something oriented towards coaching and protecting children. However, the imposition of sanctions for children can not be effective because of conflicting legal rules, law enforcement officials who have different paradigms in guarding the legal process against children, facilities and infrastructure that are incomplete and inadequate, making it difficult to enforce sanctions on children as well as the poor stigmatization of society against children in conflict with the law.